Stomata-mediated interactions between plants, herbivores, and the environment - Lin, Po-An; Chen, Yintong; Ponce, Gabriela; Acevedo, Flor E.; Lynch, Jonathan P.; Anderson, Charles T.; Ali, Jared G.; Felton, Gary W. (Trends in plant science, 2022)
Stomata play a central role in plant responses to abiotic and biotic stresses. Existing knowledge regarding the roles of stomata in plant stress is centered on abiotic stresses and plant–pathogen interactions, but how stomata influence plant–herbivore interactions remains largely unclear. Here, we summarize the functions of stomata in plant–insect interactions and highlight recent discoveries of how herbivores manipulate plant stomata. Because stomata are linked to interrelated physiological processes in plants, herbivory-induced changes in stomatal dynamics might have cellular, organismic, and/or even community-level impacts. We summarize our current understanding of how stomata mediate plant responses to herbivory and environmental stimuli, propose how herbivores may influence these responses, and identify key knowledge gaps in plant–herbivore interactions. Plant stomata are emerging as important mediators of interactions between plants and herbivores.Several components in the oral secretions of herbivores, such as enzymes and phytohormones, that can trigger herbivory-induced stomatal closure have been identified.Recent evidence suggests that herbivory-induced stomatal changes play important roles in mediating interactions among plants, herbivores, pathogens, and the environment.